Copycat Television: Globalisation, Program Formats, and Cultural Identity - Moran, Albert (University of Luton Press, 1998)
"Addressing both the scope and the significance of television program format transferthe practice of using the basic idea of a program to produce a new version of that programthis book details this rapidly growing area of the international television distribution system. Also addressed is the remaking of a program by the television industry of another nation, highlighting issues of meaning and cultural identity of national audiences."
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Océanie (lieu de production du savoir); Allemagne (corpus analysé); Australie (corpus analysé); Australie (lieu de production du savoir); Pays-Bas (corpus analysé); _Nettoyé